Factors affecting sonographic preoperative local staging of endometrial cancer. (May 2014) - Fischerova, D.; Frühauf, F.; Zikan, M.; Pinkavova, I.; Kocián, R.; Dundr, P.; Nemejcova, K.; Dusek, L.; Cibula, D.
ABSTRACT Objectives To identify major factors in the under‐ and overestimation of cervical and myometrial invasion by endometrial cancer at preoperative staging by ultrasound. Methods This prospective study involved all patients with histologically confirmed endometrial cancer referred consecutively for surgical staging between January 2009 and December 2011. All patients underwent transvaginal ultrasound examination, obtaining metric and perfusion data, and the results were compared with final histology: myometrial invasion was defined at histology in the final pathology report as being either < or ≥ 50%, while cervical stromal invasion was reported as being either present or absent, and sonographic over‐/underestimation was determined relative to these. Results Enrolled prospectively into the study were 210 patients. The proportion of cases with sonographic underestimation, relative to final histology, of myometrial invasion (i.e. false‐negative estimation of no or superficial invasion < 50%) and of cervical invasion (i.e. false‐negative finding of absence of stromal invasion) was comparable: 8.6% (n = 18) and 10.5% (n = 22), respectively. Myometrial invasion was overestimated by ultrasound (i.e. false‐positive estimation of deep invasion ≥ 50%) in 15.7% (n = 33) of cases, and cervical invasion was overestimated (i.e. false‐positive finding of presence of stromal invasion) in 4.8% (n = 10) of cases. These outcomes correspond to positive and negative predictive values of 67.6% (95% CI, 57.7–76.6) and 83.3% (95% CI, 74.9–89.8), respectively, for the subjective assessment of myometrial invasion, and 60.0% (95% CI, 38.2–79.2) and 88.1% (95% CI, 82.5–92.4), respectively, for that of cervical stromal invasion. The staging error in subjective assessment was not related to body mass index (BMI), to the position of the uterus in the pelvis or to image quality. Cervical and myometrial invasion were more often underestimated in well‐differentiated endometrial cancers that were smaller in size, with thick minimum tumor‐free myometrium and lower perfusion, and more often overestimated in moderately and poorly differentiated cancers that were larger in size, with thin minimum tumor‐free myometrium and richer perfusion. Conclusion The accuracy of subjective assessment of myometrial and cervical invasion by ultrasound was significantly influenced by tumor size, density of tumor vascularization, tumor vessel architecture and histological grading, while it was not significantly affected by BMI, uterine position and image quality. Copyright © 2013 ISUOG. Published by John Wiley & Sons Ltd.